2018
DOI: 10.1002/ceas.12109
|View full text |Cite
|
Sign up to set email alerts
|

Counselor Educators' Experiences Preparing Preservice School Counselors: A Phenomenological Study

Abstract: The authors conducted a phenomenological study to explore the experiences of 32 school counselor educators preparing preservice school counselors. Analysis of data from 3 focus groups revealed 3 themes: breadth versus depth, balancing specialties and professor partiality, and preparation versus practice. These results highlight the need for collaboration across counseling specialties at the preservice level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…Therefore, many courses in Master's degree studies in school counseling were found to lack depth in the contents they impart to future counselors. They also contribute to the discrepancy between preparations for the profession and the actual job (Perusse, Goodnough, & Noel, 2001;Watkinson et al, 2018). As attested by the counselors in the current study:…”
Section: (B) Evaluation Of the Academic Facultymentioning
confidence: 72%
See 1 more Smart Citation
“…Therefore, many courses in Master's degree studies in school counseling were found to lack depth in the contents they impart to future counselors. They also contribute to the discrepancy between preparations for the profession and the actual job (Perusse, Goodnough, & Noel, 2001;Watkinson et al, 2018). As attested by the counselors in the current study:…”
Section: (B) Evaluation Of the Academic Facultymentioning
confidence: 72%
“…Some of the incompatibility between the topics taught in the training courses for school counselors to the actual profession in the field may stem from the faculty's lack of knowledge or professionalism in school counseling tracks, as most of the lecturers do not come from this field. Study programs for an academic degree in other countries also focus more on clinical counseling for mental health than on school counseling (Bridgeland & Bruce, 2011;Watkinson, Goodman-Scott, Martin, & Biles, 2018). Most of the lecturers in the school counseling track do not come from the field of counseling and have no experience in schools and therefore do not significantly ascribe to the current trends in school counseling or in methods employed in the courses.…”
Section: (B) Evaluation Of the Academic Facultymentioning
confidence: 99%
“…The variation described in the present study parallels previous literature while also adding new insight. First, other researchers also found differences across school counselor preparation programs based on several factors including credit hours, courses, and field placements (Goodman-Scott, 2015; Goodman-Scott et al, 2016; Pérusse et al, 2015; Warren et al, 2020; Watkinson et al, 2018). These discrepancies across preparation programs were attributed to differences in faculty philosophy, identity, and preferences; state certification/licensure requirements; local school counseling job openings; and student enrollment.…”
Section: Discussionmentioning
confidence: 99%
“…These discrepancies across preparation programs were attributed to differences in faculty philosophy, identity, and preferences; state certification/licensure requirements; local school counseling job openings; and student enrollment. Researchers also have found discrepancies between school counselor preparation and practice (Goodman-Scott, 2015; Slaten et al, 2013; Watkinson et al, 2018). For instance, Goodman-Scott (2015) found that the job expectations reportedly taught in school counselor preparation programs differed from school counselors’ actual activities.…”
Section: Discussionmentioning
confidence: 99%
“…Conceptual contributions included advocacy for the counselor-advocatescholar model (Ratts & Greenleaf, 2018), a framework for intersectionality (Chan, Cor, & Band, 2018), and integration of creative thinking and problem-solving across the curriculum (McCarthy, 2018). School counselor educators presented focus group data regarding school counselor preparation (Watkinson, Goodman-Scott, Martin, & Biles, 2018) and three options for integrating evidence-based approaches within programs (Zyromski, Dimmitt, Mariani, & Griffith, 2018). Finally, Schmidt, Havlik, and Malott (2018) explored development of undergraduate counseling minors.…”
Section: Professional Issuesmentioning
confidence: 99%